Evaluation of the Efficacy of Commercial Disinfectants against African Swine Fever Virus - Lorraine Frost; Matthew Tully; Linda Dixon; Hayley M. Hicks; Jessica Bennett; Isobel Stokes; Laura Marsella; Simon Gubbins; Carrie Batten (Pathogens, 2023)
African swine fever (ASF) is an economically important disease due to high morbidity and mortality rates and the ability to affect all ages and breeds of pigs. Biosecurity measures to prevent the spread of the causative agent, African swine fever virus (ASFV), include prescriptive cleaning and disinfection procedures. The aim of this study was to establish the biocidal effects of twenty-four commercially available disinfectants including oxidizing agents, acids, aldehydes, formic acids, phenol, and mixed-class chemistries against ASFV. The products were prepared according to the manufacturer’s instructions and a suspension assay was performed with ASFV strain, BA71V using Vero cells (African green monkey cells) to test efficacy in reducing ASFV infection of cells. Generally, disinfectants containing formic acid and phenolic compounds, as well as oxidizing agents reduced viral titers of ASFV by over 4 log10 at temperatures ranging from 4 °C to 20 °C. Hydrogen peroxide, aldehyde, and quaternary ammonium compounds containing disinfectants were cytotoxic, limiting the detection of viral infectivity reductions to less than 4 log10. These preliminary results can be used to target research on disinfectants which contain active ingredients with known efficacy against ASFV under conditions recommended for the country where their use will be applied.